Myofascial pain with referred pain and its relation to headache attributed to temporomandibular dysfunction - Tonial, Leandro (Headache Medicine, 2024)
Myofascial pain with referred pain refers to any type of pain in the craniofacial region that is perceived in an anatomically different location from the original site of pain. This non-odontogenic pain is typically referred from the masticatory and cervical muscles and can manifest in the teeth, ear, face, anterior region of the head, jaw, and temporomandibular joint (TMJ). According to the ICHD-3 classification (2018), headache attributed to temporomandibular joint is considered a secondary headache, where jaw movement or pressure applied to the TMJ or surrounding musculature often exacerbates the headache. The objective of this study was to investigate the correlation between myofascial pain with referred pain and headache attributed to TMJ dysfunction in patients from a temporomandibular dysfunction clinic. An observational cross-sectional study was conducted using data from patients at the professional master's program in temporomandibular dysfunction (TMD) and orofacial pain at São Leopoldo Mandic University – Campinas, from 2015 to 2021, with a sample of 1059 clinical records. Collected data included patient gender, age group, and clinical diagnosis based on the TMD diagnostic criteria (DC). Results showed that the highest prevalence of headache attributed to TMJ dysfunction occurred in females aged 41 to 60 years old, and a significant correlation was detected between age and diagnosis of headache attributed to TMJ dysfunction, which was inversely proportional. Among the classifications, myofascial pain with referred pain stood out, affecting 425 participants. Of these, when data were analyzed in paired form, it was found that 152 participants were also diagnosed with headache attributed to TMJ dysfunction. Testing the correlation between the variables of presence of myofascial pain with referred pain and headache attributed to TMJ dysfunction revealed a significant directly proportional correlation. It is crucial for healthcare professionals to be aware of clinical possibilities, such as the formation of myofascial trigger points, with myofascial pain with referred pain being a trigger for headache attributed to TMJ dysfunction. This awareness can help avoid unnecessary treatments for pain management.